2007
DOI: 10.1590/s0004-28032007000300014
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic mucosal resection of early gastric cancer: initial experience with two technical variants

Abstract: The relatively small series presented here suggests that the method is safe and feasible. Appropriate patient selection is the most important criteria. Long follow-up is required after treatment due to the risk of relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…Macroscopic analysis of early-stage tumors according to the JSGE classification showed that most patients had type IIc lesions, followed by type III, but the difference was not significant. The present results agree with studies demonstrating a predominance of type IIc in early-stage tumors (7,18,24,26) . It should be noted that in the present study the frequency of early gastric cancer was low, accounting for only 5.2% of all tumors diagnosed.…”
Section: Discussionsupporting
confidence: 93%
“…Macroscopic analysis of early-stage tumors according to the JSGE classification showed that most patients had type IIc lesions, followed by type III, but the difference was not significant. The present results agree with studies demonstrating a predominance of type IIc in early-stage tumors (7,18,24,26) . It should be noted that in the present study the frequency of early gastric cancer was low, accounting for only 5.2% of all tumors diagnosed.…”
Section: Discussionsupporting
confidence: 93%
“…The fi rst seven cases were resected using the strip biopsy technique and the latter six cases were resected using a technical variant of ERSHE (hypertonic saline epinephrine solution) with circumferential incision. Both the en-bloc and curative resection rates were 69% [12]. There were two patients with perforations who received conservative treatment with good outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…Since 2002 we have performed endoscopic resection for the treatment of EGC in our institution [12]. During the fi rst years we used the technique proposed by Tada et al [3] and the technical variant proposed by Hirao et al [4] (ERHSE) with circumferential incision.…”
Section: Conclusion When Adequately Indicated Esd Is a Safe And Feamentioning
confidence: 99%
“…This can make the procedures prolonged and technically difficult to perform. Although reports have shown gastric aspiration mucosectomy and strip biopsy to be safe for mucosal‐based lesions in expert centres, 8,15,16 reports of experience with these techniques for gastric neoplasia arising from the submucosa are limited 17,18 . The novel use of the MBM method described enabled multiple tumors (a common characteristic of type I gastric carcinoids) to be efficiently removed and retrieved with only one re‐intubation once the initial endoscopic assessment had been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Although reports have shown gastric aspiration mucosectomy and strip biopsy to be safe for mucosal-based lesions in expert centres, 8,15,16 reports of experience with these techniques for gastric neoplasia arising from the submucosa are limited. 17,18 The novel use of the MBM method described enabled multiple tumors (a common characteristic of type I gastric carcinoids) to be efficiently removed and retrieved with only one re-intubation once the initial endoscopic assessment had been performed. It should also be noted that the widespread distribution of these lesions throughout the stomach (Table 1) shows the effectiveness of the MBM technique, which is not limited to just one area of the stomach.…”
Section: Discussionmentioning
confidence: 99%